Intervención fisioterapéutica en paciente masculino de 82 años, con síndrome del túnel tarsiano. - Vélez Contreras, Genesis Evelyn (2023)
This clinical case study focused on the treatment of an 82-year-old patient diagnosed with Tarsal Tunnel Syndrome. The main objective was to determine the effectiveness of the physiotherapy intervention in this elderly patient, taking into account its safety and tolerance. Various physical therapy treatment modalities were explored and considerations for customizing the therapeutic approach were identified. The results underlined that an individualized physical therapy, which included manual therapy, strengthening exercises, nerve stimulation and gait correction, managed to reduce pain, improve mobility and increase the quality of life of the geriatric patient. This approach not only benefited the specific case, but also provided valuable knowledge for geriatric physiotherapy in similar situations. As a key recommendation, the importance of applying individualized approaches in the treatment of elderly patients with Tarsal Tunnel Syndrome is emphasized, with the aspiration of implementing these findings in clinical practice to improve care for this population.